Enhancing Effective Classroom Management in Schools: Structures for Changing Teacher Behavior. (May 2017) - Mitchell, Barbara S.; Hirn, Regina G.; Lewis, Timothy J.
Effective classroom instructional and behavior management is essential to ensure student academic and social success. Foundational strategies such as clear expectations and routines, specific feedback, and high rates of opportunities to respond have strong empirical support, yet are often missing from educator repertoires. In this article, the authors provide a brief rationale for the inclusion of evidence-based practices accompanied with recommended resources to identify current and future practices. In addition, they also provide an overview of effective in-service educator professional development, to ensure evidence-based practices are implemented with fidelity, and recommended systemic strategies that schools and school districts can adopt to support teacher learning. Implications for teacher preparation programs also are discussed.